Condomínios verticais residenciais na cidade de São Paulo (2000-2008): condomínios-clube - Sampaio, Giuliana Beatriz Dalfovo do Amaral (2010)
This work analyze the vertical residential condominiums in Sao Paulo, which are receiving the name Condominium-Club , the name given to them by the real estate market for advertising. Some categories have been developed by the marketing consisting of possible attributes of architectural typologies. Among them are the comfort, safety and leisure. The study analyzes the phenomenon of success and dedication of these enterprises in the city of Sao Paulo. The clipping time covers the period from 2000 to 2008, justifying the selection of a form when the market is heated by the supply of credit and capital for construction and real. The central question addressed in this work is the social and collective dimension of the areas of recreation in the form of use, this in such ventures, as well as architectural features and space found, investigating whether recreational areas have actually functions disclosed as attractive for purchase and sale of residential units. The objects selected for analysis are vertical residential condominiums that are presented in the description, chosen in different areas of the city in order to characterize the phenomenon in neighborhoods that have similar conditions for their deployment. These are ventures in land area with between 10,000 and 20,000, with three or more towers, containing area of recreation and use multifamiliar.